Decrease in prevalence but increase in frequency of non-marijuana drug use following the onset of the COVID-19 pandemic in a large cohort of young men who have sex with men and young transgender women. (1st June 2021) - Janulis, Patrick; Newcomb, Michael E.; Mustanski, Brian
Highlights: No change observed in prevalence or frequency of marijuana use. A decrease of non-marijuana drug use was observed. A slight increase in frequency of non-marijuana drug use was observed. Abstract: Background: Substantial concern exists regarding the impact of the COVID-19 pandemic on substance use behaviors. This is especially true for subpopulations like young men who have sex with men and young transgender women (YMSM-YTW) who report higher rates of substance use. This study examines changes in prevalence and frequency of marijuana and non-marijuana drug use among YMSM-YTW following the onset of the pandemic. Method: Data for this analysis (n = 458 participants, 1356 observations) come from an ongoing longitudinal cohort study of YMSM-YTW. A series of Bayesian multilevel models were used to examine change in prevalence and frequency of use for marijuana and non-marijuana drugs. Results: Results indicated no systematic change in prevalence or frequency of marijuana use. However, a decrease in non-marijuana drug use was observed (OR = 0.60, 95 % CrI: [0.37, 0.94]) following the onset of the pandemic. Furthermore, a small increase in the frequency of non-marijuana drug use was observed (OR = 1.79, 95 % CrI: [1.02, 3.21]) among individuals who used these substances. Conclusions: These findings concur with a small number of studies identifying a decrease in drug use prevalence but increase in frequency among those who continue to use drugs. Despite the protective effect of lower drug use prevalence, higher frequency of use may lead to additional negative health outcomes of drug use, particularly among groups facing multiple health challenges such as YMSM-YTW. However, the pandemic likely has a unique impact on substance use behaviors across subpopulations.